(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The paper considers the need to acquire knowledge in the field of computer science from teachers of musical disciplines. Digitalization of music education and the use of modern digital instruments, keyboard synthesizer and music computer, multimedia equipment, tablet technologies are tools of the digital environment that allow teaching music disciplines at a higher level, not to the detriment of traditional classical education. There is a need to introduce the course "Music Informatics" into the system of professional training of teachers-musicians.